Analisis Urf Terhadap Tradisi Pecotan Dalam Walimatul ‘Urs Di Kecamatan Kotaanyar Kabupaten Probolinggo Provinsi Jawa Timur - Muhammad Zainuddin; Ali, Alfin Haidar; Adawiyah, Robiatul (ASASI: Journal of Islamic Family Law, 2024)
The majority of people in Kotaanyar Regency use the pecotan tradition as a medium of invitation in carrying out walimatul 'urs to invite people to attend and donate in return in the form of money or goods. However, in the current situation, people continue to preserve the pecotan tradition, even though some people feel forced to do it. This is interesting for researchers to study and examine more deeply the status of the Pecotan Tradition using the 'urf analysis approach on walimatul 'urs in Kotaanyar District, Probolinggo Regency, East Java Province. The results of this research indicate that the status of the Pecotan Tradition using the 'urf analysis approach in walimatul 'urs has fulfilled the requirements to become a tradition ('urf) and is in accordance with the law. So it can be implemented in social life because it has a good goal by helping each other between communities when implementing Walimah al-'urs.